2020
DOI: 10.7717/peerj.9638
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism underlying the effect of illumination time on the growth performance of broilers via changes in the intestinal bacterial community

Abstract: The circadian rhythms associated with light have important effects on the growth, metabolism, immunity and reproduction of broilers. However, there is a lack of systematic evaluations of the effect of the light cycle on intestinal microbes and the nutritional metabolism of these microbes in broilers. This study was designed to study the effects of the light cycle on the intestinal bacterial community structure and growth of broilers. In this study, Arbor Acre (AA) broilers were fed under a short photoperiod (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Regarding chemical composition, increased growth rates have been associated with increased fat deposition ( Tůmová and Teimouri, 2010 ). Namely, the increase in the light hours has been found to increase melatonin synthesis, inhibit the synthesis of insulin, and promote the synthesis of glucagon, favoring lipogenesis ( Wang et al, 2020 ), which is consistent with the higher lipid meat content we found in chickens kept under the standard-light regime compared to those submitted to a shorter daylight period. In contrast, other authors ( Tuell et al, 2020 ; Kim et al, 2022 ) did not report changes in meat chemical composition associated with the photoperiod.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding chemical composition, increased growth rates have been associated with increased fat deposition ( Tůmová and Teimouri, 2010 ). Namely, the increase in the light hours has been found to increase melatonin synthesis, inhibit the synthesis of insulin, and promote the synthesis of glucagon, favoring lipogenesis ( Wang et al, 2020 ), which is consistent with the higher lipid meat content we found in chickens kept under the standard-light regime compared to those submitted to a shorter daylight period. In contrast, other authors ( Tuell et al, 2020 ; Kim et al, 2022 ) did not report changes in meat chemical composition associated with the photoperiod.…”
Section: Discussionsupporting
confidence: 81%
“…Photoperiod can impact broiler performances from embryo phase to marketing time [29] . Previous studies usually compare the differences in production performance and physiology of broilers under different light regimes to select an appropriate photoperiod [30][31][32][33] . Several commonly used lighting systems (12L:12D, 16L:8D, 20L:4D) [34] and the 16L:8D regiment are the most commonly used intermediate values [35] .…”
Section: Discussionmentioning
confidence: 99%